Evaluation of Bachelor Degree of Electrical Engineering Curriculum at Vongchavalitkul University in the Academic Year 2022 - Ketthanom, Chitpong; Suppatoomsin, Chompoo; Artmeeyanant, Patcharin; Vilailak, Krisada; Khodpun, Nopphadon (Journal of Vongchavalitkul university, 2023)
Objective: This study intended to evaluate the Bachelor Degree of Electrical Engineering Curriculum at Vongchavalitkul University in the Academic Year 2022. Methods: Applying quantitative and qualitative research, the research sample used in this research was a total of 51 individuals, including 5 curriculum instructors, 8 guest instructors and other department instructors, 27current students, and 11 employers. The sample group was selected by stratified random sampling. The research instruments consisted of structured interviews and questionnaires with the index of item objective congruence (IOC) of 0.963 for curriculum instructors, 0.967 for guest instructors and instructors from other departments, 0.953 for students, and 1.00 for employers. Descriptive statistics, frequency, percentage, mean, and standard deviation were used for data analysis. Results: The findings of the research indicated that opinions on the context, input factors, processes, and outcomes were rated by curriculum instructors, guest instructors, special instructors, instructors from other departments, students, and employers at high levels.